From plant to probe: semi-synthesis of labelled undecaprenol analogues allows rapid access to probes for antibiotic targets. Issue 61 (3rd July 2020) - Cochrane, Rachel V. K.; Alexander, Francesca M.; Boland, Coilín; Fetics, Susan K.; Caffrey, Martin; Cochrane, Stephen A.
Abstract : Extraction of undecaprenol from bay leaves followed by synthetic modification is a convenient method to obtain novel chemical probes. Abstract : Undecaprenol-containing glycolipids (UCGs) are essential precursors of bacterial glycopolymers and glycoproteins. We report a novel semi-synthetic strategy to prepare labelled UCGs directly from undecaprenol. This one-size-fits-all approach offers a concise and efficient method for obtaining labelled-UCGs, which will allow new mechanistic studies and inhibitor screens to be performed on novel antibiotic targets.